THE EFFECTIVENESS OF THE ONLINE REGISTRATION SYSTEM ON THE WAITING TIME FOR OUTPATIENT SERVICES OF AL ITTIHAD HOSPITAL IN BLITAR REGENCY: English - Tri Wulandari, Tri Wulandari; Wening Palupi Dewi (Journal of Hospital Management and Services, 2025)
The hospital provides healthcare services including outpatient, inpatient, and emergency services, as well as patient medical records. An agreement-based registration system is now increasingly important to improve efficiency and reduce costs. Online enrollment helps patients avoid long queues, in contrast to the time-consuming manual system. Long wait times affect the image, quality, and satisfaction of hospital services. This study assesses the effectiveness of the online registration system on the waiting time for outpatient registration at Al Ittihad Hospital. This study used an experimental design with two post-test-only groups, measuring the effectiveness of the online registration system on outpatient waiting time at Al Ittihad Hospital, Blitar Regency. The population was the entire outpatient, with samples calculated using the Slovin formula and purposive sampling methods. The independent variable is the online enrollment system, and the dependent variable is the patient's wait time. Data were collected by questionnaire and analyzed using SPSS, including validity, reliability, normality, coefficient of determination, and t-test. This study showed that the online registration system significantly reduced the outpatient waiting time at Al Ittihad Hospital, with a tally of 5,281 greater than ttable 1,656 and alpha 0.000 < 0.05. The T-test indicates that patients who use online systems have a shorter waiting time than conventional methods. These results support the zero (Ho) hypothesis that online registration systems affect wait times.